2019
DOI: 10.18051/univmed.2019.v38.164-171
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia enhances self-renewal properties and markers of mesenchymal stem cells

Abstract: Background<br />Mesenchymal stem cells (MSCs) are multipotent stromal cells that express CD73, CD90, and CD105 surface markers, but not CD14, CD45, CD34, CD11b, and HLA-DR. MSCs under hypoxic conditions have the essential role of maintaining the stemness capacity by releasing several growth factors into their medium, known as hypoxia conditioned medium (HCM). This study was performed to compare the effect of percentage of HCM to normoxic medium (NM) in increasing MSC proliferation marked by proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, the prolonged inflammatory phase causes impaired fibroblast differentiation that leads to delayed wound contraction, potentially resulting in scar formation [6], [7]. Recent studies have shown that hypoxic mesenchymal stem cells (HMSCs) enhance wound healing acceleration in several damaged tissues by increasing growth factors such as vascular endothelial growth factor, TGF-β, and PDGF to activate fibroblast differentiation into myofibroblasts [8], [9], [10], [11]. However, there are no reports on how days the HMSCs increase wound closure to the optimum wound healing by controlling α-SMA expression released by myofibroblast.…”
Section: Introductionmentioning
confidence: 99%
“…However, the prolonged inflammatory phase causes impaired fibroblast differentiation that leads to delayed wound contraction, potentially resulting in scar formation [6], [7]. Recent studies have shown that hypoxic mesenchymal stem cells (HMSCs) enhance wound healing acceleration in several damaged tissues by increasing growth factors such as vascular endothelial growth factor, TGF-β, and PDGF to activate fibroblast differentiation into myofibroblasts [8], [9], [10], [11]. However, there are no reports on how days the HMSCs increase wound closure to the optimum wound healing by controlling α-SMA expression released by myofibroblast.…”
Section: Introductionmentioning
confidence: 99%
“…HMSCs-CM has been shown enhance the quantities of paracrine factors leading to the optimum tissue healing improvement Yustianingsih, et al, 2019). The one mechanism healing of HMSCs-CM is to promotes the enhancement of angiogenesis and re-epithelization in injured tissues, that is in part mediated by several soluble factors such as VEGF (Muhar, et al, 2019;Xia, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells derived from apical papilla of wisdom teeth also showed increased proliferation and upregulation of SSEA4 which is an embryonic stem cell marker surface antigen. Human umbilical cord derived MSC grown in a culture under 5% oxygen showed better proliferation and maintenance of stemness [65]. MSC derived from different sources showed increased expression of pluripotency markers Oct4, C-Myc and Nanog when cultured at 5% oxygen concentration levels [66].…”
Section: Hypoxic Preconditioning Improves Regenerative Potential Of Cmentioning
confidence: 98%